Case Report: Primary Pulmonary Angiosarcoma With Brain Metastasis - Tang, Xiangjun; Zhu, Jing; Zhu, Fangcheng; Tu, Hanjun; Deng, Aiping; Lu, Junti; Yang, Minghuan; Dai, Longjun; Huang, Kuanming; Zhang, Li (Frontiers in Bioengineering and Biotechnology, 2022)
Primary pulmonary angiosarcoma (PPA) is an extremely rare malignant vascular tumor. It has no specific clinical manifestation and is challenging to diagnose early. Here, we report a case of PPA with brain metastasis. A 21-year-old patient hospitalized for a head injury. Cranial MRI showed multiple intracranial lesions with brain edema. Pulmonary CT displayed bilateral pulmonary infection with mediastinal lymph node enlargement. After anti-tuberculosis treatment, the patient's symptoms progressively aggravated, accompanied by epileptic seizures, coughing and phlegm mixed with blood. The treatment was ineffective and the patient’s condition deteriorated sharply, leading to a coma. It took less than three months from symptom onset to death. PPA with brain metastasis was confirmed by autopsy.